PredMHC: An Effective Predictor of Major Histocompatibility Complex Using Mixed Features - Chen, Dong; Li, Yanjuan (Frontiers in Genetics, 2022)
The major histocompatibility complex (MHC) is a large locus on vertebrate DNA that contains a tightly linked set of polymorphic genes encoding cell surface proteins essential for the adaptive immune system. The groups of proteins encoded in MHC play an important role in the adaptive immune system. Therefore, the accurate identification of MHC is necessary to understand its role in the adaptive immune system. An effective predictor called PredMHC is established in this paper to identify MHC from protein sequences. Firstly, PredMHC encode a protein sequence with mixed features including 188D, APAAC, KSCTriad, CKSAAGP and PAAC. Secondly, three classifiers including SGD, SMO and RandomForest are trained on the mixed features of protein sequence. Finally, the prediction result is obtained by the voting of the three classifiers. The experimental results of the 10-fold cross-validation test in training dataset showed that PredMHC can obtain 91.85% accuracy. Experimental results on comparison with other features, classifiers and existing methods show the effectiveness of PredMHC in predicting MHC.